Isolated Splenic Metastases of Her2+++ Gastroesophageal Junction Adenocarcinoma - Sigrand, Julie (Case Rep Oncol, 2016)
Isolated metastases from gastric adenocarcinoma to the spleen are very infrequent. Usually, there are multiple metastases from gastric cancer, and isolated splenic metastases are very rare [Lam and Tang: Arch Pathol Lab Med 2000;124:526–530] because of certain anatomical and physiological characteristics (e.g., angulation between the splenic artery and celiac trunk, paucity of afferent lymph flow toward the spleen, contractility of the spleen and major immune content). Here, we report 2 cases of isolated splenic metastases from an adenocarcinoma of the gastroesophageal junction, both with long-term survival outcome and overexpression of Her2.